Allogeneic hematopoietic stem cell transplantation in adults with myelodysplastic syndrome: Experience of the Argentinean Group of Bone Marrow Transplantation (GATMO). Issue 3 (15th March 2016) - Basquiera, Ana L.; Rivas, María M.; Remaggi, Guillermina; Klein, Graciela; Milovic, Vera; Foncuberta, M. Cecilia; Saba, Silvia; Milone, Jorge H.; Arbelbide, Jorge; Jaimovich, Gregorio; Rolón, Juliana Martínez; Kusminsky, Gustavo; et al.
Abstract : Introduction : Allogeneic hematopoietic stem cell transplantation (AHSCT) is a curative approach for patients with myelodysplastic syndrome (MDS). Methods : In this multicenter retrospective study, we analyzed the outcome of adult patients with MDS who underwent AHSCT in Argentina and evaluated the prognostic factors associated with progression-free survival (PFS), overall survival (OS), cumulative incidence (CI) of relapse, and non-relapse mortality (NRM). Results : We analyzed data from 87 adults (median age: 43 years, range 18–66) who underwent SCT after myeloablative ( n  = 60) or non-myeloablative conditioning ( n  = 27), and from related ( n  = 62) or unrelated ( n  = 25) donors. For all patients, unadjusted 4-year PFS and OS were 37% and 38%, respectively; no significant differences were found between recipients of related or unrelated donors. One-year CI of relapse and NRM were 21% and 20%, respectively. In the multivariate analysis, intermediate disease risk index (DRI) and acute graft versus host disease AGVHD of all grades (I–IV) were independent variables associated with better PFS and lower relapse CI; only intermediate DRI was associated with better OS. Conclusions : AHSCT is a feasible procedure in Argentina, with more than 30% of the patients achieving long-term survival. Recipients with unrelated donors had at least similar outcome than those with related donors. DRI may be useful to identify patients at higher risk of relapse after transplantation.